HASIL BELAJAR SISWA KELUARGA MIGRAN - Taufiqurrohman Taufiqurrohman; Wahjoedi Wahjoedi; Punadji Setyosari (Graduate School of Universitas Negeri Malang, 2017)
This study aims to explore information on how the learning outcomes and how the students learn that both parents become migrant workers. Researchers become part of SMPN 2 Jenggawah to carry out research. Research subjects in this study were students of class VIII and IX SMPN 2 Jenggawah whose parents became migrant workers out of town or abroad, amounting to 13 students. Data analysis used is descriptive qualitative analysis, while the type of research is case study. The result of the research is the IPS score of MYR students increased from 83 to 85. The total score on the report card also increased, ie from 909 with an average of 82.63 to 918 with an average of 83.45. Differences in attitudes between parents in the overseas area with grandparents who live at home cause learning outcomes obtained by children is less satisfactory. Such grandparents' attitudes make children lazy to learn. Although children get less than satisfactory learning outcomes, children have achievements in other areas, namely the head of the intra-school student organization (OSIS) and soccer players.9Penelitian ini bertujuan untuk menggali informasi bagaimana hasil belajar dan cara belajar siswa yang kedua orangtuanya menjadi tenaga migran. Peneliti menjadi bagian dari SMPN 2 Jenggawah untuk melaksanakan penelitian. Subjek penelitian dalam penelitian ini adalah siswa kelas VIII dan IX SMPN 2 Jenggawah yang kedua orangtuanya menjadi tenaga migran ke luar kota maupun ke luar negeri yang berjumlah 13 siswa. Analisis data yang digunakan adalah analisis deskriptif kualitatif, sedangkan jenis penelitiannya adalah studi kasus. Hasil penelitiannya adalah nilai IPS siswa MYR mengalami kenaikan, yaitu dari 83 menjadi 85. Nilai total pada rapor juga mengalami kenaikan, yaitu dari 909 dengan rata-rata 82,63 menjadi 918 dengan rata-rata 83,45. Perbedaan sikap antara orangtua di daerah perantauan dengan kakek nenek yang tinggal di rumah menyebabkan hasil belajar yang didapat oleh anak kurang memuaskan. Sikap kakek dan nenek yang demikian menyebabkan anak malas untuk belajar. Meskipun anak mendapatkan hasil belajar yang kurang memuaskan, namun anak mempunyai prestasi dalam bidang yang lain yaitu ketua organisasi siswa intra sekolah (OSIS) dan pemain sepak bola.